Analisis Genetic Gain Ikan Nila Pandu (Oreochromis niloticus) antara generasi f4 dan f5 Pada umur 5 bulan - Idewani, Yosia; Basuki, Fajar (Journal of Aquaculture Management and Technology, 2013)
The purpose of this research is to compare the growth of the 4th generation (F4) and the 5th generation (F5) of Pandu tilapia and to determine the genetic gain value of Pandu tilapia from the F4 generation to the F5 generation at the age of 5 months. This research took place in Janti Freshwater Fish Hatchery and Aquaculture Unit, Klaten, in October-November 2012. The fish samples were males and females of F4 and F5 generation Pandu tilapia at the age of 4 months. This research applied 2 treatments and 3 replications for each sex, the F4 and F5 generations for male Pandu tilapia and also the F4 and F5 generations for female Pandu tilapia. The rearing treatment lasted in 30 days. The variables measured were weight, total length, thickness, survival rate, specific growth rate, relative growth rate, feed convertion ratio, and genetic gain of each variable. The results of this research indicate that the growth of F5 Pandu tilapia is better than F4 Pandu tilapia. The genetic gain value of Pandu tilapia from F4 to F5 generation at the age of 5 months are as follows, weight genetic gain : male (♂) 30,56 % and female (♀) 27,90 %; total length genetic gain : male (♂) 9,64 % and female (♀) 1,71 %; thickness genetic gain : male (♂) 13,26 % and female (♀) 11,71 %; survival rate (SR) genetic gain : male (♂) 1,89 % and female (♀) 2,75 %; specific growth rate (SGR) genetic gain : male (♂) 12,81 % and females (♀) 10,84 %; feed convertion ratio (FCR) genetic gain : male (♂) 0,78 % and females (♀) 0,63 %.